How to Calculate Crystallite Size from X-Ray Diffraction (XRD) using Scherrer Method - Siti Fatimah; Risti Ragadhita; Dwi Fitria Al Husaeni; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia (UPI), 2022)
X-Ray Diffraction (XRD) has been developed to analyze a crystal structure in the material. XRD is then improved for determining and identifying the presence of a compound, crystallinity, and crystal properties. XRD works by observing the ray refraction pattern as a result of the beam being refracted by a material that has an atomic arrangement in its crystal lattice. Until now, there is less information regarding detailed information on how to read the XRD spectrum and peak. This study aims to demonstrate how to calculate and interpret the crystallite size based on the XRD spectra. The step-by-step method in the calculation based on the XRD data is presented, which can help especially students and first-time users in understanding XRD results. This study is prospective to be used as standard information on how to read and interpret XRD spectra.